Literature review: the views of Chinese and international scholars on the causes of the US-China trade war - Chen, Yawei; Ahmad, Abdul Mua’ti @Zamri; Mahamed, Mastura; Kasimon, Diyana (Scientific research Publishing, 2022)
This study collected articles (2018-2021) on the US-China trade war, including 71 in the WOS database and 57 in the CNKI database (originating from China), and analyzed the viewpoints of international and Chinese scholars on the causes of the US-China trade war. The results show that both international and Chinese scholars have basically the same views when analyzing and considering the problems. They both believe that the trade deficit between the US and China is the direct cause of the trade war, while US trade protectionism and the “America First” mentality are the main reasons. They also agree that competition for global economic leadership between the two countries is the main root of the trade war. However, the difference between them is that international scholars generally have broader academic horizons, more objective and fair expressions, and more critical traditions. They tend to take a neutral position in analyzing the causes of the trade war. They point out not only the causes and consequences of the trade war, but also possible misjudgments by the United States. Chinese scholars, on the other hand, have relatively narrower academic horizons, their views are often nationalistic, and their narratives are more intense and emotional.